2022
DOI: 10.2147/opto.s364010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Visual Impairment and the Impact of Low Vision Assessment in a Tertiary Academic Hospital in Jordan

Abstract: Purpose This project aims to describe the characteristics of patients with visual impairment referred from a tertiary academic hospital in Jordan for a comprehensive low vision evaluation and to study its impact on their functional needs. Methods A retrospective analysis of the records of 108 patients from the ophthalmology clinic at Jordan University Hospital over the period from January 2014 to December 2018 was performed. Gathered information included age, gender, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…The result was compatible with the study of Omar et al (2008) which reported that the main cause of low vision of their patients was retinal diseases (55.5%), followed by optic nerve diseases (23.1%). This high proportion of retinal disease was consistent with many previous studies conducted in either developing countries (Thailand, Iran and Jordan) or developed countries (Australia and the United Kingdom) (Abu-Yaghi et al, 2022;Chong et al, 2016;Chotikavanich et al, 2018;Pardhan & Mahomed, 2002;Qutishat et al, 2021;Ramezani et al, 2012).…”
Section: The Aetiology Of the Low Vision And Blind In Lvc Sibu Hospitalsupporting
confidence: 91%
“…The result was compatible with the study of Omar et al (2008) which reported that the main cause of low vision of their patients was retinal diseases (55.5%), followed by optic nerve diseases (23.1%). This high proportion of retinal disease was consistent with many previous studies conducted in either developing countries (Thailand, Iran and Jordan) or developed countries (Australia and the United Kingdom) (Abu-Yaghi et al, 2022;Chong et al, 2016;Chotikavanich et al, 2018;Pardhan & Mahomed, 2002;Qutishat et al, 2021;Ramezani et al, 2012).…”
Section: The Aetiology Of the Low Vision And Blind In Lvc Sibu Hospitalsupporting
confidence: 91%